Intermittent PTH administration and mechanical loading are anabolic for periprosthetic cancellous bone. Issue 2 (18th November 2014) - Grosso, Matthew J.; Courtland, Hayden‐William; Yang, Xu; Sutherland, James P.; Stoner, Kirsten; Nguyen, Joseph; Fahlgren, Anna; Ross, F. Patrick; van der Meulen, Marjolein C. H.; Bostrom, Mathias P.
ABSTRACT The purpose of this study was to determine the individual and combined effects on periprosthetic cancellous bone of intermittent parathyroid hormone administration (iPTH) and mechanical loading at the cellular, molecular, and tissue levels. Porous titanium implants were inserted bilaterally on the cancellous bone of adult rabbits beneath a loading device attached to the distal lateral femur. The left femur received a sham loading device. The right femur was loaded daily, and half of the rabbits received daily PTH. Periprosthetic bone was evaluated up to 28 days for gene expression, histology, and µCT analysis. Loading and iPTH increased bone mass by a combination of two mechanisms: (1) Altering cell populations in a pro‐osteoblastic/anti‐adipocytic direction, and (2) controlling bone turnover by modulating the RANKL‐OPG ratio. At the tissue level, BV/TV increased with both loading (+53%, p < 0.05) and iPTH (+54%, p < 0.05). Combined treatment showed only small additional effects at the cellular and molecular levels that corresponded to a small additive effect on bone volume (+13% compared to iPTH alone, p > 0.05). This study suggests that iPTH and loading are potential therapies for enhancing periprosthetic bone formation. The elucidation of the cellular and molecular response may help further enhance the combined therapy and related targeted treatment strategies. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:163–173, 2015.